Current understanding of modes of action of multicomponent bioactive phytochemicals: potential for nutraceuticals and antimicrobials - Wink, Michael (Annual review of food science and technology, 2022)
Plants produce a diversity of plant secondary metabolites (PSMs), which function as defense chemicals against herbivores and microorganisms but also as signal compounds. An individual plant produces and accumulates mixtures of PSMs with different structural features using different biosynthetic pathways. Almost all PSMs exert one or several biological activities that can be useful for nutrition and health. This review discusses the modes of action of PSMs alone and in combinations. In a mixture, most individual PSMs can modulate different molecular targets; they are thus multitarget drugs. In an extract with many multitarget chemicals, additive and synergistic effects occur. Experiments with the model system Caenorhabditis elegans show that polyphenols and carotenoids can function as powerful antioxidative and longevity-promoting PSMs. PSMs of food plants and spices often exhibit antioxidant, anti-inflammatory, and antimicrobial properties, which can be beneficial for health and the prevention of diseases. Some extracts from food plants and spices with bioactive PSMs have potential for nutraceuticals and antimicrobials.
Gesehen am 13.06.2022